2007
DOI: 10.1158/1055-9965.epi-06-0784
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Aerobic Exercise Training on Estrogen Metabolism in Premenopausal Women: A Randomized Controlled Trial

Abstract: Background: Regular physical activity may alter estrogen metabolism, a proposed biomarker of breast cancer risk, by shifting metabolism to favor production of 2-hydroxyestrone (2-OHE1). Few studies, however, have examined this question using a randomized controlled trial. Purpose: To examine the effects of 12 weeks of aerobic exercise training on 2-OHE1 and 16A-hydroxyestrone (16A-OHE1) in premenopausal women. Methods: Participants were healthy, regularly menstruating, Caucasian women, 20 to 35 years, body mas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
4

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(27 citation statements)
references
References 41 publications
1
22
0
4
Order By: Relevance
“…Aromatization is stimulated bearing an excessive adipose mass, especially in the thighs, buttocks and abdominal-pelvic regions (gynoid obesity, sharing features with high endomorphism), with a high intake of Ω-6 polyunsaturated fatty acids (PUFAs) and having increased circulating glucocorticoids (McTernan et al, 2002) A recent study suggested that the ratio of 2/16-α-hydroxyestrogen metabolites may be a marker for lifestyle influences on estrogen metabolism associated with westernization (Falk et al, 2005). In particular, body composition was associated with 2-α-and 16-α-OHestrone levels: while thicker skinfolds were associated with higher 16-α-OH levels, (Campbell et al, 2005) an increase in lean body mass was associated with an improvement in 2/16-α-OH estrogens ratio (Campbell et al, 2007). Women who metabolize a large proportion of their estrogens via the 16-α-hydroxylation pathway could be at a higher risk of BC (Cauley et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Aromatization is stimulated bearing an excessive adipose mass, especially in the thighs, buttocks and abdominal-pelvic regions (gynoid obesity, sharing features with high endomorphism), with a high intake of Ω-6 polyunsaturated fatty acids (PUFAs) and having increased circulating glucocorticoids (McTernan et al, 2002) A recent study suggested that the ratio of 2/16-α-hydroxyestrogen metabolites may be a marker for lifestyle influences on estrogen metabolism associated with westernization (Falk et al, 2005). In particular, body composition was associated with 2-α-and 16-α-OHestrone levels: while thicker skinfolds were associated with higher 16-α-OH levels, (Campbell et al, 2005) an increase in lean body mass was associated with an improvement in 2/16-α-OH estrogens ratio (Campbell et al, 2007). Women who metabolize a large proportion of their estrogens via the 16-α-hydroxylation pathway could be at a higher risk of BC (Cauley et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…The latter pathways are considered more oestrogenic and possibly genotoxic, whereas the 2-hydroxylation pathway can promote apoptosis, anti-inflammatory actions and inhibition of tumour growth 162 172 173. However, despite body fat playing a role,162 174 epidemiological studies have not shown physical activity to alter this pathway 175 176…”
Section: Discussionmentioning
confidence: 99%
“…A randomized controlled trial concluded that a 12-week aerobic exercise training intervention did not alter oestrogen metabolism in premenopausal women [21].…”
Section: Biological Mechanismmentioning
confidence: 99%